Children's preferences for schoolyard features and understanding of ecosystem service innovations – a study in five Swedish preschools. Issue 3 (3rd July 2021) - Almers, Ellen; Askerlund, Per; Samuelsson, Tobias; Waite, Sue
ABSTRACT: This study was carried out within a project to promote health and ecosystem services, 'the benefits people obtain from ecosystems', in preschools in Sweden. The paper applies the concept 'affordance' to capture the functional meaning that children assign to different material aspects of their schoolyards before and after the installation of additional environmental features. The findings from walk-and-talks with 23 preschool children highlight what features children preferred in their yards and why. Few children showed spontaneous attention to the installed features, e.g. insect hotels. This might be more because children were not enough involved within the schoolyard development and experienced little guided exploration of environmental affordances, rather than a lack of interest per se. Given this, we suggest that development projects to upgrade schoolyards for improved ecosystem services should involve children in the design of the ecosystem services promoting features throughout the development work, and thereby, integrally, promote ecological literacy.